2019
DOI: 10.1094/mpmi-05-18-0122-r
|View full text |Cite
|
Sign up to set email alerts
|

Secretome Analysis and In Planta Expression of Salivary Proteins Identify Candidate Effectors from the Brown Planthopper Nilaparvata lugens

Abstract: The brown planthopper (BPH), Nilaparvata lugens (Stål), is a phloem sap-feeding insect. During the feeding on rice plant, BPH secretes salivary proteins with potential effector functions, which may play a critical role in the plant-insect interactions. However, a limited number of BPH effector proteins have been identified to date. Here, we sequenced the salivary gland transcriptomes of five BPH populations and subsequently established a N. lugens secretome consisting of 1140 protein-encoding genes. Secretome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 75 publications
2
79
0
Order By: Relevance
“…The C‐terminal region of this protein induces defense responses in plant cells, including cell death, the expression of pathogen‐responsive genes, and callose deposition (Shangguan et al, ). Salivary sheaths directly contact with plant cell after secretion and are easier sharped by natural selection (Rao et al, ). Because of their “forward” role in herbivore–plant interactions, salivary sheaths may undergo a higher evolution rate than other salivary components.…”
Section: Function Of Saliva In Planthopper–plant Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The C‐terminal region of this protein induces defense responses in plant cells, including cell death, the expression of pathogen‐responsive genes, and callose deposition (Shangguan et al, ). Salivary sheaths directly contact with plant cell after secretion and are easier sharped by natural selection (Rao et al, ). Because of their “forward” role in herbivore–plant interactions, salivary sheaths may undergo a higher evolution rate than other salivary components.…”
Section: Function Of Saliva In Planthopper–plant Interactionsmentioning
confidence: 99%
“…Suppression of ANX‐5 has negative effects on planthopper feeding (Huang et al, ). Interestingly, ANXs, which constitute the second largest protein family in N. lugens (Rao et al, ), do not possess typical annexin structure. These secretory ANX structures have so far been found only in planthopper species, indicating that ANXs were important in planthopper–plant coevolution.…”
Section: Function Of Saliva In Planthopper–plant Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many insect effectors have been described over the years as from saliva or salivary gland proteomic and transcriptomic data [27][28][29][30][31] . To unveil the actions of effector proteins on insect-hosts interactions, RNA interference (RNAi) has been applied.…”
mentioning
confidence: 99%
“…S4c). This suggested that the salivary DNase II may function differently from other salivary effectors such as Nl12, Nl40, Nl16, Nl28 and Nl43 (Rao et al, 2019).…”
Section: Researchmentioning
confidence: 99%